Global variation in the beta diversity of lake macrophytes is driven by environmental heterogeneity rather than latitude. (27th February 2017) - Alahuhta, Janne; Kosten, Sarian; Akasaka, Munemitsu; Auderset, Dominique; Azzella, Mattia M.; Bolpagni, Rossano; Bove, Claudia P.; Chambers, Patricia A.; Chappuis, Eglantine; Clayton, John; de Winton, Mary; Ecke, Frauke; et al.
Abstract: Aim: We studied global variation in beta diversity patterns of lake macrophytes using regional data from across the world. Specifically, we examined (1) how beta diversity of aquatic macrophytes is partitioned between species turnover and nestedness within each study region, and (2) which environmental characteristics structure variation in these beta diversity components. Location: Global. Methods: We used presence–absence data for aquatic macrophytes from 21 regions distributed around the world. We calculated pairwise‐site and multiple‐site beta diversity among lakes within each region using Sørensen dissimilarity index and partitioned it into turnover and nestedness coefficients. Beta regression was used to correlate the diversity coefficients with regional environmental characteristics. Results: Aquatic macrophytes showed different levels of beta diversity within each of the 21 study regions, with species turnover typically accounting for the majority of beta diversity, especially in high‐diversity regions. However, nestedness contributed 30–50% of total variation in macrophyte beta diversity in low‐diversity regions. The most important environmental factor explaining the three beta diversity coefficients (total, species turnover and nestedness) was elevation range, followed by relative areal extent of freshwater, latitude and water alkalinity range. Main conclusions: Our findings show that global patterns in beta diversity of lake macrophytes are caused by species turnover rather than by nestedness. These patterns in beta diversity were driven by natural environmental heterogeneity, notably variability in elevation range (also related to temperature variation) among regions. In addition, a greater range in alkalinity within a region, likely amplified by human activities, was also correlated with increased macrophyte beta diversity. These findings suggest that efforts to conserve aquatic macrophyte diversity should primarily focus on regions with large numbers of lakes that exhibit broad environmental gradients.